A REALISTIC ANALYSIS OF CONFLICTS IN POLITICAL DEBATES MUSTANSIRIYAH UNIVERSITY - Kadhim, Saad Badi (Journal of Learning on History and Social Sciences, 2025)
Objective: The current study aims to explore the conflictive speech acts used in political arguments as a tool of persuasion to undermine Russia's role and attitudes as a prominent participant in foreign policy and a large economic power. Method: Using conflictive language, the American president attempts to isolate Russia from the rest of the world, characterising it as a terrorist state intent on attacking not only Ukraine but all of the world's countries. Results: This part is not explicitly mentioned in the original text, but you could infer that the results would focus on how the use of conflictive speech acts shapes the perception of Russia in global discourse. Novelty: The novelty lies in the examination of how political leaders use conflictive speech acts as a strategic tool in international relations and foreign policy, specifically targeting Russia.